Violence conjugale, excuses patriarcales et défense de provocation - Côté, Andrée (Criminologie, 1996)
Canadian law provides many excuses for men who commit crimes of violence against women; this article analyses the defence of provocation, in light of the Common Law's historical bias in favour of male domination and of the current judicial treatment of conjugal femicide. The statutory defence of provocation partially excuses murder committed in a fit of anger, if the accused lost his self-control and if the legal authority is of the opinion that an "ordinary man", in the same circumstances, would also have been provoked by the victim to the point of losing his self-control and killing his spouse. Past and present case-law indicates that a threat to a man's right to sexually appropriate a woman is the paradigmatic foundation of this defence in cases of conjugal femicide. The plausibility of the "crime of passion" scenario is supported by popular culture and and by interpretative techniques that decontextualize the crime and render it susceptible to mythologization. The idea that men who commit crimes of violence against women "lose control" of themselves is a myth that has been debunked by social science research, but that lives on in the imagination of the legal profession. But why should we excuse crimes committed by men in anger, on a morbid desire to control "their" woman, but refuse to acknowledge the person who killed out of fear, or compassion ?